The Tax Treatment of Interest Expenditures of Multinational Enterprises - Joulia Ossokina; Herman Vollebergh (Tinbergen Institute, 2000)
This paper analyses the national tax treatment of interestexpenditures of multinational enterprises in a non-cooperative world. It is shown that the international tax systemgenerally leads to distortions in the capitaldecisions of multinational firms. In contrast to the existingliterature on the tax treatment of the expendituresof multinationals, it is found that the form and size of distortionscan differ per country depending on the stakea country has in the multinational. Furthermore, internationalisationof the firm's operations and ownership isdemonstrated to lead to less generous interest deduction rules ofindividual countries and in the limit mayresult in no deduction allowance at all.
Keywords: F21; F23; H21; H32; 330; International Investment; Multinational Firms; Optimal Taxation; Interest Expenditures; R&D Expenditures; Multinationales Unternehmen; Zins; Kapitalkosten; Unternehmensbesteuerung; Kapitalertragsteuer; Theorie